Does Information Affect Homophily? - Yana Gallen; Melanie Wasserman (Center for Economic Studies and ifo Institute (CESifo), 2022)
It is common for mentorship programs to use race, gender, and nationality to match mentors and mentees. Despite the popularity of these programs, there is little evidence on whether mentees value mentors with shared traits. Using novel administrative data from an online college mentoring platform connecting students and alumni, we document that female students indeed disproportionately reach out to female mentors. We investigate whether female students make costly trade-offs in order to access a female mentor. By eliciting students' preferences over mentor attributes, we find that female students are willing to trade off occupational match in order to access a female mentor. This willingness to pay for female mentors declines to zero when information on mentor quality is provided. The evidence suggests that female students use mentor gender to alleviate information problems, but do not derive direct utility from it. We discuss the implications of these results for the design of initiatives that match on shared traits.
Keywords: J16; J24; J71; 330; homophily; mentorship; preference elicitation; gender